THE IMPACT OF THE ASSOCIATION BETWEEN PERIODONTITIS AND CORONAVIRUS DISEASE INFECTION ON ORAL AND SYSTEMIC COMPLICATIONS. REVIEW - Alexandru Flondor; Maria-Alexandra Martu; Liliana Pasarin; George-Alexandru Maftei; Oana Ciurcanu; Vasilica Toma; Silvia Martu; Ionut Luchian (Romanian Society of Oral Rehabilitation, 2022)
Several risk factors have been associated with severe coronavirus disease and include factors such as advanced age and sex (male) and comorbidities such as obesity and the presence of underlying diseases (eg, hypertension, cardiovascular disease, cerebrovascular disease, chronic kidney disease, and diabetes). These predisposing conditions share several standard features that could explain why they are associated with worse disease outcomes. Persistent and uncontrolled inflammation is a key manifestation of several diseases, such as periodontitis, cardiovascular diseases, neurodegenerative diseases, diabetes, and coronavirus disease infection. The oral cavity is a reservoir for respiratory pathogens, especially among patients with poor oral hygiene and periodontitis, and dysregulated inflammatory and immune response. In fact, periodontal pockets in the elderly have been associated with increased risk of mortality from pneumonia, and periodontitis patients are more likely to develop hospital-acquired, pneumonia than healthy ones are. Conclusions; Periodontitis shares several common features with coronavirus disease including similarities in comorbidities and effects on systemic inflammation. However, further research would be needed to confirm these hypotheses.